Kaon condensation and lambda-nucleon loop in the relativistic mean-field approach - Maruyama, T.; Muto, T.; Tatsumi, T.; Tsushima, K.; Thomas, A. W. (Elsevier B.V., 2005)
The possibility of kaon condensation in high-density symmetric nuclear matter is investigated including both s- and p-wave kaon-baryon interactions within the relativistic mean-field (RMF) theory. Above a certain density, we have a collective (D) over bar (S) state carrying the same quantum numbers as the antikaon. The appearance of the (K) over bar (S) state is caused by the time component of the axial-vector interaction between kaons and baryons. It is shown that the system becomes unstable with respect to condensation of K-(K) over bar (S) pairs. We consider how the effective baryon masses affect the kaon self-energy coming from the time component of the axial-vector interaction. Also, the role of the spatial component of the axial-vector interaction on the possible existence of the collective kaonic states is discussed in connection with A-mixing effects in the ground state of high-density matter: Implications of K (K) over bar (S) condensation for high-energy heavy-ion collisions are briefly mentioned. (c) 2005 Elsevier B.V. All rights reserved.